2021
DOI: 10.1186/s13104-021-05778-3
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of strategies to promote healthy dietary choices in UK secondary school canteens: a qualitative study

Abstract: Objective To explore the acceptability and feasibility of choice architecture strategies for dietary change in UK secondary school canteens from the perspectives of pupils, school staff and catering providers through qualitative focus groups and interviews. Results Three focus groups with adolescents (n = 15; mean age 13.7 years; standard deviation 1.9) and eight interviews with school staff and caterers recruited from one school and catering provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Consistent with other recent studies [43,53], a mismatch between individual budgets and food prices (as an environmental factor) influences students' decision to settle on food outlets offering cheaper food options. The mismatch impels young people to focus on the need for quantity and satiety as found for adolescents in Coventry, U.K. [54]. Even though cheaper food options per-se may not necessarily be unhealthy [42,55], there is overwhelming evidence suggesting that cheap foods are generally not healthy or sustainable with healthy foods found to be largely expensive [56] and especially in LICs [57].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other recent studies [43,53], a mismatch between individual budgets and food prices (as an environmental factor) influences students' decision to settle on food outlets offering cheaper food options. The mismatch impels young people to focus on the need for quantity and satiety as found for adolescents in Coventry, U.K. [54]. Even though cheaper food options per-se may not necessarily be unhealthy [42,55], there is overwhelming evidence suggesting that cheap foods are generally not healthy or sustainable with healthy foods found to be largely expensive [56] and especially in LICs [57].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a US study, the majority of adolescents (93.7%) reported taste as important when they were selecting food items in the school canteen (65) . Similarly, in a UK study, taste was reported as a priority among adolescents (69) . Therefore, this may create challenges to encouraging adolescents to choose healthier items in school, as research suggests that adolescents tend to associate healthier options with being of poorer taste (54,69,70) .…”
Section: Taste Preferences Visual Appeal Familiarity and Food Qualitymentioning
confidence: 79%
“…Similarly, in a UK study, taste was reported as a priority among adolescents (69) . Therefore, this may create challenges to encouraging adolescents to choose healthier items in school, as research suggests that adolescents tend to associate healthier options with being of poorer taste (54,69,70) . UK school catering staff have also shared the view that adolescents are seen to opt for the less healthy items and have expressed concerns that excluding these unhealthy foods from the school lunch menu would severely compromise their sales (71) .…”
Section: Taste Preferences Visual Appeal Familiarity and Food Qualitymentioning
confidence: 79%
See 2 more Smart Citations